Fluorine-containing polyimide-based composite solid electrolyte, preparation method thereof and lithium battery
Through chemical imidation method and nanofiltration membrane suction filtration technology, the problem that FPI and SN-based electrolytes cannot be blended is solved, and a porous composite electrolyte membrane is prepared, which improves the rate performance and mechanical properties of lithium-ion batteries and enhances the electrolyte Ion conductivity and thermal stability extend the cycle life of the battery.
Patent Information
- Application Number
- CN202411071780.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-06
AI Technical Summary
FPI and SN-based electrolytes cannot be blended, resulting in the inability to prepare a uniform electrolyte membrane. SN as a plasticizer will reduce mechanical properties, limiting the rate performance and mechanical properties of lithium-ion batteries.
Fluoropolyimide is prepared by chemical imidation method, and crosslinking agent is added to crosslink it internally, and then filtration is performed on a nanofiltration membrane and soaked in anhydrous ethanol to form a porous composite crosslinked fluoropolyimide. The amine electrolyte membrane solves the compatibility problems of SN and FPI and improves mechanical properties.
It significantly improves the rate performance of lithium-ion batteries and the mechanical properties of the electrolyte membrane, enhances the ionic conductivity and thermal stability of the electrolyte, extends the cycle life of the battery, and improves the electrochemical performance.
Smart Images

Figure CN119133587A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a fluorine-containing polyimide-based composite solid electrolyte, a preparation method thereof, and a lithium battery. Background Art
[0002] Lithium-ion batteries have been widely used in new energy vehicles, energy storage power stations and some electronic devices, such as mobile phones and computers, due to their high energy density, light weight, flexibility and long life. However, the phenomenon of spontaneous combustion and explosion of lithium batteries is frequent, which is attributed to the fact that the liquid electrolyte in lithium batteries is easy to decompose under high temperature and high voltage, thus causing explosion. Therefore, people have turned their attention to solid polymer electrolytes with excellent safety, thermal stability, electrochemical stability, flammability and mechanical strength. In addition, they have good compatibility with electrodes and can replace the role of diaphragms. PEO-based electrolytes stand out due to their high lithium ion conductivity, good processing performance and high energy density, but they still need to be improved in mechanical properties, high temperature resistance and safety performance. Polyimide materials have been favored by people because of their advantages of high temperature resistance, excellent mechanical properties, good electrochemical activity and high theoretical capacity. Fluorinated polyimide (FPI) can further improve processing performance, increase the dielectric constant of the material, enhance the surface polarity of the membrane, have good compatibility with the electrode interface, reduce the crystallinity of the polymer, promote the dissociation of Li+ and reduce the volume resistance. However, they have very low ionic conductivity (10 -11 Up to 10 -5 S / cm), which has led to the search for a new composite electrolyte design to enhance the ionic conductivity of FPI-based SPE.
[0003] Succinonitrile (SN)-based electrolytes have great potential in the practical application of all-solid-state lithium metal batteries due to their high room temperature ionic conductivity, wide electrochemical window and good thermal stability. However, poor mechanical strength, low stability to lithium metal and poor interfacial compatibility with electrodes hinder the further application of SN-based electrolytes in all-solid-state lithium metal batteries. FPI polymer electrolytes can just make up for the disadvantages of SN electrolytes, improve mechanical properties, enhance interfacial compatibility and high stability to lithium metal. The FPI-SN-based electrolytes formed by the composite of the two are expected to become one of the directions of the design of a new generation of electrolytes, while ensuring electrical properties, mechanical properties and thermal properties. However, there are still problems in the preparation of FPI-SN-based electrolytes. The two cannot be blended because FPI and SN are not compatible. SN cannot enter the interior of FPI. The two cannot be mixed to form a uniform electrolyte membrane. In addition, SN also acts as a plasticizer, which will reduce the mechanical properties of the polymer, making it impossible for the mechanical properties to reach an ideal state. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the object of the present invention is to provide a method for preparing a fluorinated polyimide-based composite solid electrolyte, so that FPI and SN can be mixed to prepare a uniform electrolyte membrane, which significantly improves the rate performance of lithium-ion batteries and enhances the mechanical properties of the electrolyte membrane.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing a fluorinated polyimide-based composite solid electrolyte, comprising the following steps:
[0007] (1) synthesizing a fluorine-containing polyamic acid precursor solution by reacting a fluorine-containing aromatic diamine and an excess of aromatic dianhydride in an organic solvent; the molar ratio of the fluorine-containing aromatic diamine to the aromatic dianhydride is 1:(1.03-1.1);
[0008] (2) adding a silane coupling agent to the fluorinated polyamic acid precursor solution prepared in step (1) to obtain a chemically cross-linked fluorinated polyamic acid solution;
[0009] (3) adding acetic anhydride and pyridine to the chemically cross-linked fluorinated polyamic acid solution prepared in step (2) to perform chemical imidization to obtain a cross-linked fluorinated polyimide solution; adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide) to the cross-linked fluorinated polyimide solution to obtain a composite cross-linked fluorinated polyimide solution;
[0010] (4) preparing a film from the composite cross-linked fluorinated polyimide solution obtained in step (3) to obtain a composite cross-linked fluorinated polyimide electrolyte membrane; the mass percentage of the organic solvent in the composite cross-linked fluorinated polyimide electrolyte membrane is 84-85%;
[0011] (5) placing a nanofiltration membrane on a sand core filter plate of a sand core funnel, placing the composite cross-linked fluorinated polyimide electrolyte membrane prepared in step (4) on the nanofiltration membrane, performing suction filtration to extract the organic solvent in the composite cross-linked fluorinated polyimide electrolyte membrane, and then soaking it in anhydrous ethanol to obtain a porous composite cross-linked fluorinated polyimide electrolyte membrane;
[0012] (6) After removing the solvent from the porous composite cross-linked fluorinated polyimide electrolyte membrane obtained in step (5), thermal cross-linking is performed under vacuum conditions to obtain a fluorinated polyimide-based composite solid electrolyte.
[0013] Preferably, the fluorine-containing aromatic diamine in step (1) has one of the following structures:
[0014]
[0015]
[0016] The fluorine-containing aromatic dianhydride has one of the following structural formulas:
[0017]
[0018] Preferably, the organic solvent in step (1) is N,N-dimethylformamide.
[0019] Preferably, the silane coupling agent in step (2) is one of bis(3-trimethoxysilylpropyl)amine, N-[3-(trimethoxysilyl)propyl]ethylenediamine and (3-aminopropyl)triethoxysilane.
[0020] Preferably, in step (3), the molar ratio of succinonitrile: lithium bis(trifluoromethanesulfonyl)imide: fluorinated polyimide is 1:(0.5-1):(1.5-2).
[0021] Preferably, the pore size of the nanofiltration membrane in step (5) is 2 to 10 nm.
[0022] Preferably, the soaking in anhydrous ethanol in step (5) is specifically: soaking in anhydrous ethanol for 24 to 72 hours.
[0023] Preferably, in step (6), the porous composite cross-linked fluorinated polyimide electrolyte membrane obtained in step (5) is subjected to thermal cross-linking under vacuum conditions after the solvent is removed, specifically:
[0024] First, the porous composite cross-linked fluorinated polyimide electrolyte membrane obtained in step (5) is placed in a blast oven to remove the solvent, and then placed in a vacuum oven, and the temperature is raised from room temperature to 50-60°C and kept warm for 1-4 hours. After the temperature is raised to 70-80°C and kept warm for 4-8 hours, then raised to 90-100°C and kept warm for 4-8 hours, and finally raised to 110-120°C and kept warm for 1-4 hours. After thermal cross-linking, a fluorinated polyimide-based composite solid electrolyte is obtained.
[0025] The present invention also provides a fluorine-containing polyimide-based composite solid electrolyte, which is prepared by the preparation method of the fluorine-containing polyimide-based composite solid electrolyte.
[0026] The present invention also provides a lithium ion battery, comprising the fluorine-containing polyimide-based composite solid electrolyte.
[0027] Preferably, the amount of bis(3-trimethoxysilylpropyl)amine (BTMSPA) added in step (2) is 5-10% of the mass of the fluorinated polyamic acid precursor.
[0028] Preferably, the film preparation in step (4) is specifically: coating with a film applicator (scraper), film casting or film spraying with an electrostatic spinning method to obtain a composite cross-linked fluorinated polyimide electrolyte membrane containing a small amount of impurities.
[0029] Preferably, the amount of acetic anhydride added in step (3) is 16.5-17.5wt% of the composite cross-linked fluorinated polyimide electrolyte membrane; the amount of pyridine added in step (3) is 12.5-13.5wt% of the composite cross-linked fluorinated polyimide electrolyte membrane.
[0030] Preferably, when a film coating device (scraper) is used for coating in step (4), the size of the scraper is 200 to 500 μm, and the thickness of the film is between 50 and 150 μm.
[0031] Preferably, the nanofiltration membrane in step (5) is a polycarbonate nanofiltration membrane.
[0032] The principle of the present invention is:
[0033] The present invention uses a chemical imidization method to prepare a fluorinated polyimide, and by adding a crosslinking agent, crosslinking is generated inside the fluorinated polyimide, and then SN and LITFSI are dissolved in an organic solvent, added to the crosslinked polyimide solution after imidization, and then a membrane is prepared. At this time, the membrane is not dried and contains 84-85wt% of organic solvent; the obtained membrane is filtered in a sand core funnel using a nanofiltration membrane with small holes with precise pore size and uniform distribution, and most of the organic solvent can be removed, so that the composite crosslinked fluorinated polyimide membrane becomes uniformly porous, and succinonitrile and lithium salt are separated from the solvent and evenly stored inside the membrane; then it is placed in anhydrous ethanol, and while removing impurities, succinonitrile and lithium salt are further stored in the membrane by a phase separation method. In addition, while heating and drying the solvent, the membrane is thermally crosslinked, and finally a composite porous crosslinked fluorinated polyimide membrane is prepared. SN is introduced into the composite porous cross-linked fluorinated polyimide membrane prepared by the present invention. Although SN as a plasticizer reduces the mechanical properties of the system, the introduction of cross-linked FPI greatly improves the mechanical properties. In addition, when SN is used alone as an ion conductive medium, it is very unstable and easily reacts with lithium sheets or pole sheets, resulting in instability of the electrolyte system and greatly reducing the cycle life of the battery. However, after the cross-linked FPI is introduced as a three-dimensional porous skeleton, SN is uniformly dispersed in the cross-linked FPI, and the cycle life is greatly improved. Finally, since FPI has a carbonyl group, it can also exist as a positive electrode material in the electrolyte system, providing a certain amount of additional capacity for the battery.
[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0035] (1) The preparation method of the fluorinated polyimide-based composite solid electrolyte of the present invention is to place the composite cross-linked fluorinated polyimide electrolyte membrane in a sand core funnel and use a nanofiltration membrane for suction filtration, so that the composite cross-linked fluorinated polyimide electrolyte membrane becomes uniformly porous, and SN and lithium salt can be smoothly stored in the membrane, solving the problem that SN and FPI cannot be mixed and prepared.
[0036] (2) The preparation method of the fluorinated polyimide-based composite solid electrolyte of the present invention abandons the traditional method of dissolving FPI in DMAC and then blending FPI and SN, and directly adding SN to the mixture during the synthesis of the cross-linked FPI. After the imide cyclization of FPI, SN is added to the porous cross-linked fluorinated polyimide solution and mixed, so that SN is evenly mixed in the porous cross-linked polyimide. Subsequently, SN and the cross-linked FPI are filtered through a sand core funnel to form a three-dimensional porous skeleton electrolyte membrane, thereby solving the problem of incompatibility between the cross-linked FPI and SN.
[0037] (3) The preparation method of the fluorinated polyimide-based composite solid electrolyte of the present invention uses porous cross-linked FPI instead of ordinary FPI. First, it is convenient for SN to enter the FPI membrane from the pores. Second, the addition of SN reduces the mechanical properties of the system, making the three-dimensional skeleton mechanical strength insufficient and unable to effectively hinder the growth of lithium dendrites. Therefore, cross-linked FPI is used to greatly improve the mechanical properties to meet the needs of the electrolyte system.
[0038] (4) The preparation method of the fluorinated polyimide-based composite solid electrolyte of the present invention cross-links the fluorinated polyimide through a cross-linking agent, thereby greatly improving the mechanical strength and reducing the effect of SN as a plasticizer on the mechanical strength.
[0039] (5) The preparation method of the fluorinated polyimide-based composite solid electrolyte of the present invention introduces fluorine groups into polyimide, improves processing performance, increases the dielectric constant of the material, enhances the surface polarity and interface compatibility of the membrane, and promotes Li + dissociation and transport.
[0040] (6) The introduction of SN in the fluorinated polyimide-based composite solid electrolyte of the present invention greatly improves the ionic conductivity at room temperature and improves the electrochemical window, thereby greatly improving the electrical performance; the introduction of cross-linked FPI improves the mechanical properties, enhances the interface compatibility, improves the thermal stability, and promotes Li + In addition, because FPI has a carbonyl group, it can also be used as a positive electrode material when the battery is running, providing a certain amount of additional capacity to the battery, so that the battery equipped with this composite electrolyte has better electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Surface SEM image (a) of the finished composite porous cross-linked fluorinated polyimide electrolyte membrane in Example 1 of the present invention and cross-sectional SEM image (b) of the finished porous cross-linked fluorinated polyimide electrolyte membrane in Comparative Example 1 of the present invention.
[0042] Figure 2 It is a long cycle performance diagram of the electrolyte membrane of Example 1 (FPI-SN) of the present invention and Comparative Example 2 (PEO-SN) at 25°C and 0.2C.
[0043] Figure 3 It is the rate cycle diagram of 0.1C-0.2C-0.5C-1C-2-1C-0.5C-0.2C-0.1C of the electrolyte membrane of Example 1 (FPI-SN) of the present invention and Comparative Example 2 (PEO-SN) at 25 degrees.
[0044] Figure 4 1 and 2 are LSV diagrams of the electrolyte membranes of Example 1 (FPI-SN) of the present invention and Comparative Example 2 (PEO-SN) at 25°C.
[0045] Figure 5 Graphs showing the tensile properties of the electrolyte membranes of Example 1 (a) of the present invention and Comparative Example 2 (b).
[0046] Figure 6 The thermal dimensional stability test results of the electrolyte membranes of Example 1 and Comparative Example 2 of the present invention at 30°C-60°C-90°C are shown.
[0047] Figure 7 Ignition test results of the electrolyte membranes of Example 1 of the present invention and Comparative Example 2 under flame. DETAILED DESCRIPTION
[0048] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0049] Example 1
[0050] Step 1: Dissolve 0.8569 g of fluorinated diamine (TFDB) and 1.2243 g of fluorinated dianhydride (molar ratio 1:1.03, ensure that the dianhydride is slightly excessive to obtain anhydride-terminated polyamic acid oligomer) in 12 mL of N,N-dimethylformamide (DMF), stir for 12 hours in an ice-water bath under a nitrogen atmosphere, wait for the viscosity of the solution in the container to increase, and obtain a completely reacted anhydride-terminated fluorinated polyamic acid precursor solution.
[0051] Step 2: Add the crosslinking agent bis(3-trimethoxysilylpropyl) (BTMSPA) into the container
[0052] 0.1486 g, after vigorous stirring for 1 h, 2.2654 g of acetic anhydride and 1.7555 g of pyridine were then added dropwise to the solution for chemical imidization for 1.5 h to form a cross-linked fluorinated polyimide solution (C-12FPI).
[0053] Step 3: 1.0406 g of succinonitrile (SN) and 1.0406 g of lithium bis(trifluoromethylsulfonyl)imide (LITFSI) were dissolved in DMF at 50° C., then added to C-12FPI, stirred for 20 min, and then immediately poured onto a polytetrafluoroethylene plate, and coated with a surgical scraper having a size of 250 μm. After being shaped, a membrane with a DMF content of 84.6 wt% was obtained. After being torn off, it was immediately placed in a sand core funnel equipped with a polycarbonate nanofilter membrane for suction filtration, wherein the polycarbonate nanofilter membrane was placed on the sand core filter plate of the sand core funnel, and the membrane was placed on the polycarbonate nanofilter membrane; then the filtered membrane was immersed in anhydrous ethanol until it was washed to obtain a porous composite cross-linked fluorinated polyimide electrolyte membrane (C-12FPI-SN) free of impurities.
[0054] Step 4: first put the membrane into a blast oven at 80°C to remove the remaining solvent, then put it into a vacuum oven for thermal crosslinking, raise the temperature from room temperature to 55°C and keep it for 4 hours, then raise the temperature to 75°C and keep it for 8 hours, then raise the temperature to 95°C and keep it for 8 hours, and finally raise the temperature to 110-120°C and keep it for 4 hours to obtain a finished composite porous cross-linked fluorinated polyimide electrolyte membrane, that is, a fluorinated polyimide-based composite solid electrolyte.
[0055] Example 2
[0056] In this embodiment, the fluorine-containing diamine is
[0057]
[0058] In this embodiment, the fluorine-containing dianhydride is
[0059]
[0060] The steps of this embodiment are similar to those of embodiment 1, except that the diamine monomer is replaced by 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene from 2,2'-bis(trifluoromethyl)diaminobiphenyl to prepare a fluorinated polyimide-based composite solid electrolyte.
[0061] Example 3
[0062] In this embodiment, the fluorine-containing diamine is
[0063]
[0064] In this embodiment, the fluorine-containing dianhydride is
[0065]
[0066] The steps of this embodiment are similar to those of embodiment 1, except that the dianhydride monomer is replaced by 9,9-bis(trifluoromethyl)-2,3,6,7-oxanthenetetracarboxylic dianhydride from 4,4'-(hexafluoroisopropylene) diphthalic anhydride; and a fluorinated polyimide-based composite solid electrolyte is prepared.
[0067] Example 4
[0068] The steps of this embodiment are similar to those of embodiment 1, except that the cross-linking agent is replaced by (3-aminopropyl)triethoxysilane (KH550) instead of bis(3-trimethoxysilylpropyl)amine (BTMSPA), and a fluorinated polyimide-based composite solid electrolyte is prepared.
[0069] Comparative Example 1
[0070] The steps of Comparative Example 1 are similar to those of Example 1, except that SN is not added.
[0071] Comparative Example 2
[0072] The polyethylene oxide PEO (M=300000) used in this comparative example 2 is
[0073]
[0074] Step 1: Dissolve 2.0812 g of polyethylene oxide (PEO) in 15 mL of N,N-dimethylformamide, and stir at 50° C. under a nitrogen atmosphere until all PEO is dissolved and the viscosity of the solution in the container increases, thereby obtaining a PEO solution.
[0075] Step 2: Dissolve 1.0406 g of succinonitrile (SN) and 1.0406 g of lithium bis(trifluoromethylsulfonyl)imide (LITFSI) in DMF at 50°C, then add to the PEO solution and stir for 2 h. After mixing, cast the mixture onto a polytetrafluoroethylene plate and control the film thickness to be between 75 and 150 μm.
[0076] Step 3: First, place the membrane in a forced air oven at 50°C to remove the solvent, and then place it in a vacuum oven at 50°C to remove moisture, and finally obtain a composite polyethylene oxide electrolyte membrane (PEO-SN).
[0077] SEM test of electrolyte membrane:
[0078] The SEM test results of the fluorinated polyimide-based composite electrolyte membrane of Example 1 and the electrolyte membrane of Comparative Example 1 are as follows: Figure 1As shown, it can be clearly seen that both materials form a uniform porous structure, and in the embodiment with SN added, SN is better distributed in the pores of the membrane, proving that the preparation method of Example 1 can effectively mix FPI, SN and LITFSI well.
[0079] Battery cycle performance test of lithium-ion battery at 0.2C:
[0080] Comparing the lithium ion batteries using the fluorinated polyimide-based composite solid electrolyte membrane of Example 1 and the composite polyethylene oxide electrolyte membrane of Comparative Example 2, the battery cycle performance is as follows: Figure 2 As shown, compared with the traditional PEO-based composite electrolyte, the carbonyl-containing fluorinated polyimide-based composite electrolyte system has a higher specific capacity and can play a role as a part of the positive electrode in the battery; the cycle life is long, and it still has a certain specific capacity after 1500 cycles, the cycle remains stable, and the growth of lithium dendrites is suppressed to a certain extent; Figure 3 The PEO-SN curve in the figure begins to become disordered after 300 cycles, and the battery cycle is unstable.
[0081] Rate performance test of lithium-ion batteries:
[0082] Comparing the lithium ion batteries using the fluorinated polyimide-based composite solid electrolyte membrane of Example 1 and the polyethylene oxide composite electrolyte membrane of Comparative Example 2, the rate cycling performance is as follows: Figure 3 As shown, the results show that at different rates, the fluorinated polyimide-based composite solid electrolyte prepared in Example 1 of the present invention has a specific capacity far exceeding that of the system in Comparative Example 2.
[0083] LSV test of lithium-ion batteries:
[0084] The LSV test results of the lithium ion battery using the fluorinated polyimide-based composite solid electrolyte membrane of Example 1 and the polyoxyethylene composite electrolyte of Comparative Example 2 are as follows: Figure 4 As shown, it can be seen that the lithium battery assembled with the fluorinated polyimide-based composite electrolyte prepared by the embodiment of the present invention has a higher decomposition voltage than that of the polyethylene oxide composite electrolyte. The decomposition voltage in the embodiment reaches about 5.5V, while the decomposition voltage of comparative example 2 is only about 4.5V, which proves that the embodiment system has better high voltage resistance, a wider range of operating voltage, and improved safety.
[0085] Tensile test of electrolyte membrane:
[0086] Comparing the fluorinated polyimide-based composite solid electrolyte membrane of Example 1 and the polyethylene oxide-based composite electrolyte membrane of Comparative Example 2, the tensile test results are as follows: Figure 5As shown, the tensile strength of the embodiment system is 40 MPa, and the elongation is 196%, which are much larger than the tensile strength of 0.2 MPa and the elongation of 25% of the comparative example 2 system, indicating that the fluorinated polyimide-based composite electrolyte membrane has better mechanical strength, can effectively inhibit dendrite growth, prevent puncture, and has better processability and is tougher, and can be used to meet the requirements of different shapes.
[0087] Thermal dimensional stability test of electrolyte membrane:
[0088] The thermal dimensional stability test of the fluorinated polyimide-based composite solid electrolyte membrane of Example 1 and the polyethylene oxide-based composite electrolyte membrane of Comparative Example 2 is as follows: Figure 6 As shown in the figure, it can be seen that when the temperature reaches 60°C, the size of the polyethylene oxide composite electrolyte membrane has become unstable, and when the temperature reaches 90°C, it completely loses its shape. However, the fluorinated polyimide-based composite electrolyte membrane can still maintain dimensional stability at 90°C, indicating that the fluorinated polyimide-based composite electrolyte membrane is stronger in thermal stability than the polyethylene oxide composite electrolyte membrane, and its safety is improved.
[0089] Ignition test of electrolyte membrane
[0090] The fluorinated polyimide-based composite solid electrolyte membrane of Example 1 and the polyoxyethylene composite electrolyte membrane of Comparative Example 2 were compared and the ignition test results were as follows: Figure 7 As shown, it can be seen that compared with the polyethylene oxide composite electrolyte membrane, the fluorinated polyimide-based composite electrolyte membrane ignites more slowly and can still maintain a certain shape after 40 seconds. After complete combustion, it becomes a carbonized solid, while the polyethylene oxide composite electrolyte membrane burns rapidly after contacting the flame, and the combustion is completed in a very short time, turning into a black liquid. The above results effectively prove that the fluorinated polyimide-based composite electrolyte membrane has better flame retardancy, better safety performance, and is not prone to spontaneous combustion and explosion.
[0091] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a fluorinated polyimide-based composite solid electrolyte, characterized in that: The following steps are involved: (1) synthesizing a fluorine-containing polyamic acid precursor solution by reacting a fluorine-containing aromatic diamine and an excess of aromatic dianhydride in an organic solvent; the molar ratio of the fluorine-containing aromatic diamine to the aromatic dianhydride is 1:(1.03-1.1); (2) adding a silane coupling agent to the fluorinated polyamic acid precursor solution prepared in step (1) to obtain a chemically cross-linked fluorinated polyamic acid solution; (3) adding acetic anhydride and pyridine to the chemically cross-linked fluorinated polyamic acid solution prepared in step (2) to perform chemical imidization to obtain a cross-linked fluorinated polyimide solution; Adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide) into a cross-linked fluorinated polyimide solution to obtain a composite cross-linked fluorinated polyimide solution; (4) preparing a film from the composite cross-linked fluorinated polyimide solution obtained in step (3) to obtain a composite cross-linked fluorinated polyimide electrolyte membrane; the mass percentage of the organic solvent in the composite cross-linked fluorinated polyimide electrolyte membrane is 84-85%; (5) placing a nanofiltration membrane on a sand core filter plate of a sand core funnel, placing the composite cross-linked fluorinated polyimide electrolyte membrane prepared in step (4) on the nanofiltration membrane, performing suction filtration to extract the organic solvent in the composite cross-linked fluorinated polyimide electrolyte membrane, and then soaking it in anhydrous ethanol to obtain a porous composite cross-linked fluorinated polyimide electrolyte membrane; (6) After removing the solvent from the porous composite cross-linked fluorinated polyimide electrolyte membrane obtained in step (5), thermal cross-linking is performed under vacuum conditions to obtain a fluorinated polyimide-based composite solid electrolyte.
2. The method for preparing the fluorinated polyimide-based composite solid electrolyte according to claim 1, characterized in that: The fluorine-containing aromatic diamine in step (1) has one of the following structures: The fluorine-containing aromatic dianhydride has one of the following structural formulas:
3. The method for preparing the fluorinated polyimide-based composite solid electrolyte according to claim 1, characterized in that: The organic solvent in step (1) is N,N-dimethylformamide.
4. The method for preparing the fluorinated polyimide-based composite solid electrolyte for a lithium battery according to claim 1, characterized in that: The silane coupling agent in step (2) is one of bis(3-trimethoxysilylpropyl)amine, N-[3-(trimethoxysilyl)propyl]ethylenediamine and (3-aminopropyl)triethoxysilane.
5. The method for preparing the fluorinated polyimide-based composite solid electrolyte according to claim 1, characterized in that: In step (3), the molar ratio of succinonitrile: lithium bis(trifluoromethanesulfonyl)imide: fluorinated polyimide is 1:(0.5-1):(1.5-2).
6. The method for preparing the fluorinated polyimide-based composite solid electrolyte according to claim 1, characterized in that: The pore size of the nanofiltration membrane in step (5) is 2 to 10 nm.
7. The method for preparing the fluorinated polyimide-based composite solid electrolyte according to claim 1, characterized in that: The soaking in anhydrous ethanol described in step (5) is specifically: soaking in anhydrous ethanol for 24 to 72 hours.
8. The method for preparing the fluorinated polyimide-based composite solid electrolyte according to claim 1, characterized in that: Step (6) wherein the porous composite cross-linked fluorinated polyimide electrolyte membrane obtained in step (5) is subjected to thermal cross-linking under vacuum conditions after the solvent is removed, specifically: First, the porous composite cross-linked fluorinated polyimide electrolyte membrane obtained in step (5) is placed in a blast oven to remove the solvent, and then placed in a vacuum oven, and the temperature is raised from room temperature to 50-60°C and kept warm for 1-4 hours. After the temperature is raised to 70-80°C and kept warm for 4-8 hours, then raised to 90-100°C and kept warm for 4-8 hours, and finally raised to 110-120°C and kept warm for 1-4 hours. After thermal cross-linking, a fluorinated polyimide-based composite solid electrolyte is obtained.
9. A fluorinated polyimide-based composite solid electrolyte, characterized in that: The fluorinated polyimide-based composite solid electrolyte is prepared by the preparation method of any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It includes the fluorinated polyimide-based composite solid electrolyte as described in claim 9.
Citation Information
Patent Citations
Lithium-stable nanofiber-based composite solid electrolyte as well as preparation method and application thereof
CN115051028A
Preparation method of high-fluorine-content cross-linked polyimide nanofiber membrane, lithium ion battery diaphragm and lithium ion battery
CN116446109A
Microbial incubator equipped with foam removal unit
KR1020220106017A
Cited By
Photo-initiated polymerization polyimide-based composite electrolyte slurry and preparation and application thereof
CN121812719A
